2016
DOI: 10.1155/2016/2428970
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Drop in Tortuosity/Kinking of the Internal Carotid Artery: Simulation and Clinical Investigation

Abstract: Background. Whether carotid tortuosity/kinking of the internal carotid artery leads to cerebral ischemia remains unclear. There is very little research about the hemodynamic variation induced by carotid tortuosity/kinking in the literature. The objective of this study was to research the blood pressure changes induced by carotid tortuosity/kinking. Methods. We first created a geometric model of carotid tortuosity/kinking. Based on hemodynamic boundary conditions, the hemodynamics of carotid tortuosity and kink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 6 publications
0
21
0
6
Order By: Relevance
“…If a patients’ BMI increases from 20 to 30 kg/m 2 , AICATI will increase 0.67; it means that the actual length of eICA is 0.67-fold longer than straight length from the bifurcation point of the carotid artery to the point where eICA entered the carotid canal in the skull. Because eICA tortuosity may lead to a reduction in artery pressure and the level of blood pressure drop is related to the severity of tortuosity ( 4 ). It means obesity itself may cause insufficient blood flow to the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If a patients’ BMI increases from 20 to 30 kg/m 2 , AICATI will increase 0.67; it means that the actual length of eICA is 0.67-fold longer than straight length from the bifurcation point of the carotid artery to the point where eICA entered the carotid canal in the skull. Because eICA tortuosity may lead to a reduction in artery pressure and the level of blood pressure drop is related to the severity of tortuosity ( 4 ). It means obesity itself may cause insufficient blood flow to the brain.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of eICA tortuosity ranges from 4 to 66%, while eICA tortuosity accounts for 4–16% symptomatic cerebrovascular insufficiency ( 2 , 3 ). eICA tortuosity may lead to a reduction in artery pressure distal to the tortuosity, and the level of blood pressure drop is related to the severity of tortuosity ( 4 ). eICA tortuosity may also give rise to intermittent stenosis or occlusion by head rotation, trigger cerebral ischemia, and make intimal ulceration ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…DICAs can reduce the blood supply to the brain through decreases in blood pressure, which often do not lead to cerebral ischemia due to compensation of the self-regulatory mechanism in the cerebral blood supply. However, when the self-regulatory mechanism is weakened or decompensation occurs due to factors such as atherosclerosis, hypertension, diabetes or old age, cerebral ischemia can occur 18 , 19 . In fact, cerebral ischemia from DICAs occurs through two mechanisms: a thromboembolic mechanism from endothelial lesions due to changes in the local flow at the site of arterial bending, and a hemodynamic mechanism that plays an important role under both neutral and dynamic conditions 20 .…”
Section: Hemodynamicsmentioning
confidence: 99%
“…The consistency of the lesion locations across Groups 1 and 2 is compelling, but more study is needed on the mechanisms underlying this regional vulnerability. For example there may be regional differences in vessel tortuosity ( Wang et al, 2016 ) or flow rate that may predict risk factors for lesion deposition. A priori studies of the brain regions identified in this study should enable more sensitive analyses.…”
Section: Discussionmentioning
confidence: 99%